Psychopathy and Culpability: How Responsible Is the Psychopath for Criminal Wrongdoing?. Issue 1 (22nd March 2012) - Fox, Adam R.; Kvaran, Trevor H.; Fontaine, Reid Griffith
<x xml:space="preserve">Abstract</x> Recent research into the psychological and neurobiological underpinnings of psychopathy has raised the question of whether, or to what degree, psychopaths should be considered morally and criminally responsible for their actions. In this article, we review the current empirical literature on psychopathy, focusing particularly on deficits in moral reasoning, and consider several potential conclusions that could be drawn based on this evidence. Our analysis of the empirical evidence on psychopathy suggests that while psychopaths do not meet the criteria for full criminal responsibility, they nonetheless retain some criminal responsibility. We conclude, by introducing the notion of rights as correlative, that even if psychopaths were to be fully nonresponsible, imposing some form of civil commitment would still be warranted.